Information Systems Interconnection. ISDN. Provision of OSI connection-mode transport service over the OSI connection-mode network service by using an ISDN circuit-mode 64 kbit/s unrestricted bearer service. Permanent case. (30th September 1991) - British Standards Institution,
No abstract available